Design and Build a Web-Based Sumberagung Village Information System Using Php and Sql - Jiwandono, Tri Hardiyanto; Izzuddin, Ahmad; Hikmah, Nuzul (Universitas Panca Marga, 2022)
The Probolinggo Regency Government encourages every village to have a website page to makeit easier for the community to know broadly about programs and activities, as well as budget realization within the village government. In addition, the existence of a website can be used to promote the potential of the village. Although so far not all villages in Probolinggo Regency have a website, but for villages that already have internet network access, it is an obligation to have a website as a means of sharing information with the community. The purpose of this research is to design and build a system that can help the community to know the news, programs and data of Sumberagung village. This village information system uses the PHP programming language and SQL database that can make it easier for the community to get information related to the village and improve the quality and efficiency of community services. This research was conducted inseveral stages, namely the design of software using flow charts or called flowchats and software development using the waterfall model. From the results of the overall analysis of the tests carried out will determine the feasibility of the system features that have been made. Feature -System features are considered feasible if the overall test results are in accordance with the expected output. And in the tests that have been carried out by this research based on the Black Box test table above, it can be concluded that the features of the system built by the researcher can be concluded that these features have been running well and according to needs.